Tinjauan Triwulanan Perekonomian Indonesia - Tjiptoherijanto, Prijono; Surono, Sumarno; Sumarno, Sulastri; Wirakartakusumah, Djuhari; Alatas, Secha (Institute for Economic and Social Research, 1987)
.